Alexander Hamilton: founder of the American Public Administration - Green, Richard T. (2002)
This article describes the foundation of Hamilton's theory and practice of public administration. That foundation consists of four interconnected pillars: politics, organization design, ethics, and law. These pillars undergird the public administration today but are not recognized as the foundation of the field. We may be entering a period of reform in our conception of the field. If this is so, we will perhaps also reconsider the interpretation of the field's origins. Hamilton should figure prominently in any such revision for he, more than any other founder, attended to the theory and practice of public administration in the American Republic. We cannot help but practice the craft of public administration in his shadow. - Reproduced.
Keywords: Public administration; Hamilton, Alexander